Age-related impairments of mobility associated with cobalt and other heavy metals: Data from NHANES 1999-2004 - Lang, I.; Scarlett, Alan; Guralnik, J.; Depledge, M.; Melzer, D.; Galloway, T. (2009)
Exposure to heavy metals promotes oxidative stress and damage to cellular components, and may accelerate age-related disease and disability. Physical mobility is a validated biomarker of age-related disability and is predictive of hospitalization and mortality. Our study examined associations between selected heavy metals and impaired lower limb mobility in a representative older human population. Data for 1615 adults aged =60 yr from the National Health and Nutrition Examination Survey (NHANES) 1999 to 2004 were used to identify associations between urinary concentrations of 10 metals with self-reported and measured significant walking impairments. Models were adjusted for confounding factors, including smoking. In models adjusted for age, gender, and ethnicity, elevated levels of cadmium, cobalt, and uranium were associated with impairment of the ability to walk a quarter mile. In fully adjusted models, cobalt was the only metal that remained associated: the odds ratio (OR) for reporting walking problems with a 1-unit increase in logged cobalt concentration (µg/L) was 1.43 (95% CI 1.12 to 1.84). Cobalt was also the only metal associated with a significant increased measured time to walk a 20-ft course. In analyses of disease categories to explain the mobility finding, cobalt was associated with physician diagnosed arthritis (1-unit increase OR = 1.22 (95% CI 1.00 to 1.49). Low-level cobalt exposure, assessed through urinary concentrations of this essential heavy metal, may be a risk factor for age-related physical impairments. Independent replication is needed to confirm this association. Copyright © Taylor & Francis Group, LLC.